Tanggung Jawab Hukum Bagi Produsen Obat Sirup Anak yang Berbahan Zat Berbahaya Berdasarkan Undang-Undang No 17 Tahun 2023 Tentang Kesehatan - Mohammad Ginong Pratidina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The case shows that some children's syrup drug products contain hazardous substances that can endanger the health of children. As a producer of children's syrup, their legal responsibility is very important in ensuring consumer safety. Law No. 17 of 2023 concerning Health provides a legal framework that regulates the responsibility of producers in this regard. This thesis discusses the legal responsibility of producers of children's syrup containing dangerous substances based on the law. The research reviews legal aspects related to producer responsibility, including legal sanctions that can be given to producers if they are found to have violated regulations, as well as what efforts producers can take to minimize legal risks and meet product safety and quality standards. The results of the study show that manufacturers of syrup for children must pay attention to various regulations and safety and quality standards stipulated by Law No. 17 of 2023 concerning Health and related institutions, and conduct product trials periodically to ensure safety and quality. In addition, producers must also be prepared to face legal sanctions if they violate existing regulations, such as fines and revocation of business licenses. The legal responsibility of the producer, then legal liability, namely civil, criminal and administrative responsibility Legal efforts that can be carried out Mediation efforts with the business actor/manufacturer of children's syrup medicine, if this fails, then the process can be carried out through the Consumer Dispute Protection Agency (BPSK), if the decision is not satisfactory, further legal action can be taken through the general court. The Ministry of Health and BPOM should be able to mitigate risks at the outset, regarding the distribution of drugs in Indonesia